Placental DNA methylation changes in detection of tetralogy of Fallot. (1st June 2020) - Bahado‐Singh, R.; Vishweswaraiah, S.; Mishra, N. K.; Guda, C.; Radhakrishna, U.
ABSTRACT: Objectives: To determine whether the methylation level of cytosine nucleotides in placental DNA can be used to predict tetralogy of Fallot (TOF) and provide insights into the developmental mechanism of this condition. Methods: Tissue sections were obtained from formalin‐fixed paraffin‐embedded specimens of placental tissue obtained at birth from eight cases with non‐chromosomal, non‐syndromic TOF and 10 unaffected newborns. The Illumina Infinium HumanMethylation450 BeadChip assay was used to measure cytosine ('CpG' or 'cg') methylation levels at loci throughout the placental genome. Differential methylation was assessed by comparing the β‐values (a measure of the extent of cytosine methylation) for individual CpG loci in fetuses with TOF vs in controls. The most discriminating CpG sites were determined based on a preset cut‐off of ≥ 2.0‐fold change in the methylation level. The predictive accuracy of CpG loci with significant methylation changes for TOF was determined by the area under the receiver‐operating‐characteristics curve (AUC). A false‐discovery‐rate (FDR) P ‐value < 0.05 was used to define a statistically significant difference in the methylation level. Ingenuity Pathway Analysis (IPA) (Qiagen) was used to identify gene pathways that were significantly overexpressed, and thus altered, in TOF cases compared with controls. Results: We found a total of 165 significantly differentially methylated CpG loci in TOF cases compared with controls, in 165 separate genes. These biomarkers demonstrated from fair to excellent individual predictive accuracy for TOF detection, with AUCs ≥ 0.75 (FDR P ‐value < 0.001 for all). The following CpG loci (gene) had the highest predictive accuracy: cg05273049 ( ARHGAP22 ; AUC = 1.00; 95% CI, 1.00–1.00), cg02540011 ( CDK5 ; AUC = 0.96; 95% CI, 0.87–1.00), cg08404201 ( TRIM27 ; AUC = 0.95; 95% CI, 0.84–1.00) and cg00687252 ( IER3 ; AUC = 0.95; 95% CI, 0.84–1.00). IPA revealed over‐representation (dysregulation) of 14 gene pathways involved in normal cardiac development, including cardiomyocyte differentiation via bone morphogenetic protein receptors, cardiac hypertrophy signaling and role of nuclear factor of activated T cells in cardiac hypertrophy. Cardiac hypertrophy is an important feature of TOF. Conclusions: Analysis of placental DNA cytosine methylation changes yielded accurate markers for TOF detection and provided mechanistic information on TOF development. Our work appears to confirm the central role of epigenetic changes and of the placenta in the development of TOF. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.